2019
DOI: 10.1177/1471301219862942
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of dementia inclusive environmental adjustment in the emergency department

Abstract: Objectives Acute hospitals, in particular the emergency department, can be disorienting for people living with dementia. As part of a larger project to improve care for people living with dementia, dementia-inclusive modifications were made to two emergency department bays in a large acute care hospital in Ireland. Modifications to spatial configuration included noise reduction, altered lighting and the addition of an orientation aid and fixed seating for relatives. Method A mixed methods approach was employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…It is estimated that about one-third of older people in acute Irish hospitals may have dementia [7][8][9]. However, the acute hospital setting can often be experienced as disorientating and stressful by people living with dementia and previous research has indicated that this can result in adverse health and functional outcomes including the provision of insufficient care [9][10][11][12][13][14][15][16][17][18][19]. Furthermore, limited knowledge and understanding of dementia among general hospital staff, coupled with organisational constraints on a busy hospital ward and traditional task approaches to care within acute settings, can contribute to negative attitudes towards people living with dementia and challenges to the ability to provide personcentred care [11,13,14,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that about one-third of older people in acute Irish hospitals may have dementia [7][8][9]. However, the acute hospital setting can often be experienced as disorientating and stressful by people living with dementia and previous research has indicated that this can result in adverse health and functional outcomes including the provision of insufficient care [9][10][11][12][13][14][15][16][17][18][19]. Furthermore, limited knowledge and understanding of dementia among general hospital staff, coupled with organisational constraints on a busy hospital ward and traditional task approaches to care within acute settings, can contribute to negative attitudes towards people living with dementia and challenges to the ability to provide personcentred care [11,13,14,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This creates a culture of care where patient safety and risk are prioritized over patient dignity, care is disease/illness orientated and people living with dementia are seen as a low priority [13,14]. In addition, there is a lack of understanding and knowledge of person-centred care within the acute hospital setting [13] resulting in poorer experiences and outcomes for people living with dementia [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This creates a culture of care where patient safety and risk are prioritized over patient dignity, care is disease/illness orientated and people with dementia are seen as a low priority (13,14). In addition, there is a lack of understanding and knowledge of person-centred care within the acute hospital setting (13) resulting in poorer experiences and outcomes for people with dementia (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that about one-third of older people in acute Irish hospitals may have dementia (7)(8)(9). However, the acute hospital setting can often be experienced as disorientating and stressful by people living with dementia and previous research has already indicated that this can result in adverse health and well-being (10)(11)(12)(13)(14)(15)(16)(17)(18). Furthermore, limited knowledge and understanding of dementia among general hospital staff, coupled with organisational constraints on a busy hospital ward and traditional task approaches to care within acute settings, can contribute to negative attitudes towards people living with dementia and challenges to the ability to provide person-centered care (10,12,19,20).…”
Section: Introductionmentioning
confidence: 99%